The Transformation of Administrative Responsibility: A New Theory of Public Accountability in Modern Administrative Law - Marzuki (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
Administrative responsibility has long constituted one of the fundamental pillars of administrative law, serving as the primary legal mechanism through which governmental authority is constrained, public officials are held accountable, and citizens are protected against unlawful administrative action. Traditionally, administrative responsibility has been understood primarily through the lens of legal liability, emphasizing compliance with statutory authority, judicial review, and procedural legality. However, the increasing complexity of contemporary governance has exposed significant limitations within this classical understanding. The expansion of regulatory institutions, collaborative governance, independent administrative agencies, and multi-level public administration has transformed the manner in which public authority is exercised, resulting in increasingly fragmented structures of accountability that challenge conventional doctrines of administrative responsibility.This study aims to reinterpret the concept of administrative responsibility by developing a broader theoretical framework capable of explaining the distribution of public accountability within modern administrative governance. The research employs a normative legal methodology combining doctrinal analysis, comparative administrative law, and conceptual legal synthesis. Primary legal materials include administrative law principles, constitutional doctrines concerning public accountability, statutory regulations governing administrative authority, and leading scholarly literature on administrative responsibility, public governance, and accountability theory.